2012
DOI: 10.1086/665831
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Paternal Responses of Virgin Male California Mice (Peromyscus californicus): Behavioral and Physiological Correlates

Abstract: California mice Peromyscus californicus are a rodent species in which fathers provide extensive paternal care; however, behavioral responses of virgin males toward conspecific neonates vary from paternal behavior to tolerance to infanticide. Indirect evidence suggests that paternal responses might be influenced by social status potentially through increased stress and anxiety in subordinate males. To test this hypothesis, we housed 12 virgin male California mice in same-sex dyads on weaning and assessed their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…PVN AVP can facilitate activation of the hypothalamic-pituitaryadrenal axis in response to stress and promotes anxiety-related and depression-like behavior (Caldwell et al 2008). Correspondingly, in three of these studies, inter-individual differences in paternal behavior and PVN AVP expression were associated with differences in circulating corticosterone concentrations and/or anxiety-like behavior (Frazier et al 2006;De Jong et al 2012;Perkeybile et al 2013Perkeybile et al , 2015.…”
Section: Early-life Handlingmentioning
confidence: 89%
See 2 more Smart Citations
“…PVN AVP can facilitate activation of the hypothalamic-pituitaryadrenal axis in response to stress and promotes anxiety-related and depression-like behavior (Caldwell et al 2008). Correspondingly, in three of these studies, inter-individual differences in paternal behavior and PVN AVP expression were associated with differences in circulating corticosterone concentrations and/or anxiety-like behavior (Frazier et al 2006;De Jong et al 2012;Perkeybile et al 2013Perkeybile et al , 2015.…”
Section: Early-life Handlingmentioning
confidence: 89%
“…In the same species, Lambert et al (2011) found a negative correlation between the total time that virgin males spent performing paternal behavior toward an unrelated pup and the expression of the immediateearly gene Fos in the PVN, a region strongly involved in the stress response, following a 10-min exposure to the pup. Finally, De Jong et al (2012) found that latencies of adult virgin males to sniff an unfamiliar pup correlated positively with expression 6 of AVP mRNA in the PVN and negatively with urine marking in the center of a novel environment; both of these measures are considered indices of anxiety. Taken together, these findings suggest that paternal responsiveness may be inversely related to anxiety and stress-reactivity, at least in the short term.…”
Section: Stress and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…The males used in this study were selected for aggressiveness toward pups. Virgin males of the Mongolian gerbil, similar to those of the California mouse, may be aggressive, indifferent or paternal toward foreign pups of the same species (De Jong et al, 2012). The criteria for aggressive male behavior included sniffing and attacking pups and moving them violently.…”
Section: Animalsmentioning
confidence: 99%
“…This species is unusual among mammals in having a monogamous mating system with extensive male parental care and minimal sexual size dimorphism (Gubernick and Alberts 1987;Gubernick 1988;Gubernick and Teferi 2000); consequently, some aspects of its endocrinology have been described. Peromyscus californicus has unusually high baseline CORT levels for a rodent (Glasper and DeVries 2005;Harris et al 2011;Trainor et al 2011;de Jong et al 2012), as well as extremely dynamic diurnal CORT rhythms with very large changes in CORT concentration from trough to peak . As CORT is involved in mobilizing energy stores, this high baseline may be indicative of unusually high voluntary activity, with individual variation around the mean correlated with individual variation in exercise propensity or capacity.…”
Section: Introductionmentioning
confidence: 99%